Aerodynamic damping in the structural analysis of steel lattice towers - Skwarek, Marcin; Hulimka, Jacek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Structural analysis of lightweight freestanding structures, such as steel lattice towers, mainly consists of determining the along-wind dynamic response of the vibrating structure. These vibrations are damped not only structurally but also by the aerodynamic forces. In the Polish design practice, aerodynamic damping concept was introduced together with the rules of Eurocode standards. With respect to the lattice towers, in many cases, these rules are inaccurate, therefore the paper contains some suggestions of authors.